Acute and Chronic Pancreatitis 2015
DOI: 10.5772/58883
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapies on Pancreatitis

Abstract: Acute and Chronic Pancreatitis 154have long cytoplasmic processes that encircle the base of the acinus are strongly involved not only in the pathogenesis of CP but also in pancreatic cancer. They are located in the periacinar, perivascular and periductal regions of the pancreas [ , ].Over the past decades, our understanding of the pathogenesis of pancreatitis has significantly improved. "nimal models including caerulein, taurocholate, L-arginine studies are important in order to understand the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
1
0
1
Order By: Relevance
“…Key ndings included the marked inhibition of in ammatory cytokine secretion and the attenuation of pancreatic stellate cell activation. Additionally, these cells exhibited the ability to suppress pancreatitis-induced vesicular cell apoptosis, attributed to the downregulation of the PI3K signaling pathway within pancreatic tissues [23] .Several studies have also demonstrated that ucmscs may be involved in immune regulation to suppress in ammatory factors and reduce tissue brosis [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Key ndings included the marked inhibition of in ammatory cytokine secretion and the attenuation of pancreatic stellate cell activation. Additionally, these cells exhibited the ability to suppress pancreatitis-induced vesicular cell apoptosis, attributed to the downregulation of the PI3K signaling pathway within pancreatic tissues [23] .Several studies have also demonstrated that ucmscs may be involved in immune regulation to suppress in ammatory factors and reduce tissue brosis [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Существует также исследование, которое показывает, что желчные протоки являются источником стволовых клеток для поджелудочной железы, как показано Wang et al [23]. Их исследование показало, что поджелудочная и желчная системы тесно связаны друг с другом и что всегда есть стволовые клетки, которые могут дать начало определенным типам клеток поджелудочной железы, таким как протоки и железы поджелудочной железы [24].…”
Section: применение мезенхимальных стволовых клеток в лечении острого...unclassified